EARLY DISCONTINUATION OF P2Y12 ANTAGONISTS AND ADVERSE CLINICAL OUTCOMES POST PERCUTANEOUS CORONARY INTERVENTION - Daniel Harris (Journal of the American College of Cardiology, 2018)
Poster Contribution - ACC.18